2019
DOI: 10.1017/aae.2019.34
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Land Management Practices and Technical and Environmental Efficiency among Smallholder Farmers in Ghana

Abstract: The study examines the effects of adoption of sustainable land management practices on farm households’ technical efficiency (TE) and environmental efficiency, using household-level data from Ghana. We employ selectivity biased-corrected stochastic production frontier to account for potential bias from both observed and unobserved factors. The empirical results show that adopters exhibit higher levels of TE and output, compared with the nonadopters. However, the results reveal that adopters are found to use ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 35 publications
2
15
0
Order By: Relevance
“…To achieve this, the government can support cotton companies by opening vocational agricultural schools to train more advisers. Our results are also consistent with those of Issaku and Abdulai (2020), further corroborating that the adoption of the SWC techniques is profitable to farmers regardless of their area. Cotton companies must therefore insist more on the adoption of these techniques by all farmers.…”
Section: Resultssupporting
confidence: 91%
“…To achieve this, the government can support cotton companies by opening vocational agricultural schools to train more advisers. Our results are also consistent with those of Issaku and Abdulai (2020), further corroborating that the adoption of the SWC techniques is profitable to farmers regardless of their area. Cotton companies must therefore insist more on the adoption of these techniques by all farmers.…”
Section: Resultssupporting
confidence: 91%
“…Overdose application of pesticide is also reported among vegetable farmers in Tanzania 22 and among smallholder farmers in Ghana. 13 …”
Section: Introductionmentioning
confidence: 99%
“…10 Most African farmers have limited economic incentives and financial resources to afford sophisticated farm machinery to apply agrochemicals; hence they resort to the use of manual/simple farm tools such as knapsack sprayers, buckets, brushes, and brooms in the application of agrochemicals. [11][12][13] Furthermore, many farmers apply pesticides without the appropriate Personal Protective Equipment (PPE) such as nose mask, overall coats, goggles, gloves, Wellington boots, etc., which further exposes them to chemical poisoning with grievous health and environmental consequences. 14,15 According to Northern Presbyterian Agriculture Services and Partners (NPASP) 27 of Ghana, 15 farmers died because of chemical poisoning in the Upper East region of Ghana.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of Ghana, the Ghana Statistical Service [24], reveal that about 88.8% of households in Ghana rely on agricultural activities drawing on local practices. Moreover, research on local practices and climate change adaptation, have largely grown along with; the perceptions of smallholders' farmers about climate change, how smallholder farmers cope and adapt to climatic events [16,33], the vulnerability of smallholders to climate change [65], as well as the practices smallholder farmers engage in towards sustainable land management [29]. These studies have demonstrated the multiple trade-offs that smallholders in Ghana make to adapt food crops production to climate change.…”
Section: Introductionmentioning
confidence: 99%